Prospective effects of food safety trust on brand evangelism: a moderated-mediation role of consumer perceived ethicality and brand passion - Zhou Guanqi; Zeb Un Nisa (BMC, 2023)
Abstract Background The current study integrates brand management literature with food consumption research and develops an integrative framework by combining food safety trust, consumer perceived ethicality, brand evangelism, and brand passion into a single conceptual model. Method This quantitative study included 228 ready-to-eat consumers in China using purposive sampling. Data were collected at two periods in time, resulting in a time-lag study in which respondents provided data on independent and moderating variables at time 1 and mediating and dependent variables at time 2 with the same respondents from time 1. The hypothesized correlations were tested using SEM and PROCESS Macro techniques. Results According to the findings, trust in food safety has a significant impact on brand evangelism and passion. Furthermore, consumer perceived ethicality (CPE) found to have a substantial moderating role between food safety-FS and brand passion. Moreover, we validated the brand passion role as a mediator between brand evangelism and food safety trust, and investigated whether consumer perceived ethicality conditionally affects the strength of the indirect relationship among food safety trust and brand evangelism through brand passion, indicating a moderated-mediation mechanism. Originality Drawing on Sternberg theory of love, current study is the first of its kind to evaluate the boundary role as well as the conditional indirect influence of customer perceived ethicality among the study's variables and provides useful information for ready-to-eat food brand managers on how to keep them interested in their risk-free food products.